2016
DOI: 10.1161/jaha.116.004028
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Renal G Protein–Coupled Receptor Kinase Type 4 Expression via Ultrasound‐Targeted Microbubble Destruction Lowers Blood Pressure in Spontaneously Hypertensive Rats

Abstract: BackgroundG protein–coupled receptor kinase type 4 (GRK4) plays a vital role in the long‐term control of blood pressure (BP) and sodium excretion by regulating renal G protein–coupled receptor phosphorylation, including dopamine type 1 receptor (D1R). Ultrasound‐targeted microbubble destruction (UTMD) is a promising method for gene delivery. Whether this method can deliver GRK4 small interfering RNA (siRNA) and lower BP is not known.Methods and ResultsBP, 24‐hour sodium excretion, and urine volume were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
(93 reference statements)
6
12
0
Order By: Relevance
“…28 The persistent phosphorylation of GPCRs leads to their uncoupling from their G protein/effector complex and impairment of their function, D 1 R and D 3 R, for example. 25,28,[36][37][38][39] In the present study, we found that renal GRK4 expression was, indeed, increased in SHRs, which was consistent with previous studies. 25,36 Therefore, we speculated that increased GRK4 expression and/or activity may have contributed to the increased renal ETBR phosphorylation in the SHR and hGRK4γ142V transgenic mice.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…28 The persistent phosphorylation of GPCRs leads to their uncoupling from their G protein/effector complex and impairment of their function, D 1 R and D 3 R, for example. 25,28,[36][37][38][39] In the present study, we found that renal GRK4 expression was, indeed, increased in SHRs, which was consistent with previous studies. 25,36 Therefore, we speculated that increased GRK4 expression and/or activity may have contributed to the increased renal ETBR phosphorylation in the SHR and hGRK4γ142V transgenic mice.…”
Section: Discussionsupporting
confidence: 93%
“…As aforementioned, ETBR belongs to the family of GPCRs; their phosphorylation is a common mechanism that desensitizes their function. 25,27,31 Our present study found that ETBR phosphorylation is higher in kidneys from SHRs than WKY rats, which may explain the dysfunction of renal ETBR in hypertension. 17 However, this supposition needs to be confirmed, that is, decreasing the hyper-phosphorylation of ETBR, per se, should improve ETBR function and ameliorate the hypertension.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…However, repeated and prolonged steroid therapy is associated with an excess of adverse events, some of which are dose related (Zhao et al, 2015a). Previous studies confirmed that US combined with MBs could enhance the delivery of genes or drug to target areas of tissues including the kidney (Ibsen et al, 2013;Aryal et al, 2014;Huang et al, 2016;Wei et al, 2016). A recent study showed that CoQ10-liposome in combination with US and MBs could improve the protective effect of the drug on the damaged kidney as seen in diabetic nephropathy (Yue et al, 2017).…”
Section: Downloaded Frommentioning
confidence: 99%